Artificial Intelligence and Digital Marketing: Ethical Challenges of Digital Influence on Public Perception and Consumer Behavior in the Law of the UAE - yas, harith; Maha Mustafa Omer Abdalaziz; Wided Dafri; Qusay AL-Falahi; Basma Kashmoola; Adel Salem AlLouzi (Research Journal in Advanced Humanities, 2025)
This paper discusses the ethical and legal considerations of artificial intelligence (AI) in digital marketing in the fast-changing regulatory environment of the United Arab Emirates (UAE). Marketing strategies are increasingly leveraging AI technologies, including machine learning, natural language processing, and generative models, to provide personalized experiences for consumers, automate content creation, and inform data-driven decision-making. Nonetheless, this digital revolution also poses serious questions about data privacy, algorithmic bias, consumer manipulation, and transparency. Through the secondary research methodology, the article examines 85 documents comprising academic publications, government reports, and legal texts, providing a thorough review of the nexus between AI capabilities and regulatory frameworks in the UAE. The results show that although the use of AI has increased at a faster pace, especially among various generational groups of consumers, there is a need to transform the legal and ethical framework to address the arising risks. Ethical AI governance is based on the main regulations, including the UAE Personal Data Protection Law, Cybercrime Law, Consumer Protection Law, and Digital Commerce Law. Such laws are focused on transparency, consent, and accountability in AI-driven marketing activities. Additionally, explainability and fairness are key factors that make consumers trustful, but AI is usually too technical to provide meaningful transparency. The paper concludes that a moderate solution is the key, which is to incorporate technological innovation with moral governance. It demands enhanced regulation enforcement, industry self-regulation, and cultural change within organizations to guarantee responsible AI use. The future of ethical digital marketing and consumer protection in the era of intelligent automation will be influenced by the changing legal framework of the UAE.